2021
DOI: 10.1002/eji.202149263
|View full text |Cite
|
Sign up to set email alerts
|

Collagen type VI is the antigen recognized by the ER‐TR7 antibody

Abstract: Collagen type VI is the antigen recognized by the ER-TR7 antibodySince its first description published in this journal in 1984 [1], the monoclonal antibody ER-TR7 has been used in a great number of immunological and nonimmunological studies. Even so, its antigen is still unknown. The ER-TR7 (Erasmus University Rotterdam-Thymic Reticulum) antibody was originally produced in a screen aimed at identifying monoclonal antibodies reactive against nonlymphoid stromal cells of the mouse thymus [1]. Therefore, its stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 10 publications
(11 reference statements)
3
17
0
Order By: Relevance
“…After two days, cells were switched for additional 48 h in serum-free DMEM. The conditioned media were precipitated, resuspended in 2x Laemmli sample buffer and subjected to electrophoresis in 0.5% (w/ v) agarose/2.4% (w/v) polyacrylamide composite gels or in 4À12% polyacrylamide gradient gels under non reducing conditions [62]. Thyroglobulin (670 kDa) (Sigma) was used as a molecular weight standard.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…After two days, cells were switched for additional 48 h in serum-free DMEM. The conditioned media were precipitated, resuspended in 2x Laemmli sample buffer and subjected to electrophoresis in 0.5% (w/ v) agarose/2.4% (w/v) polyacrylamide composite gels or in 4À12% polyacrylamide gradient gels under non reducing conditions [62]. Thyroglobulin (670 kDa) (Sigma) was used as a molecular weight standard.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Indeed, some remarkable facts point in this direction. For instance, tolerance induction in mice increases the abundance of collagen VI present in the T-cell zone in LNs [90,104]. On the other side, antibodymediated targeting of collagen VI in mouse models resulted in reduced tolerance induction and enhanced graft rejection, correlating with altered migration of alloreactive T cells and T regulatory cells to the cortical ridge ECM structure at the interphase between the T-and B-cell zone [90,105].…”
Section: Dystrophic Epidermolysis Bullosamentioning
confidence: 99%
“…For example, the antibody Erasmus University Rotterdam‐thymic reticulum antibody 7 (ER‐TR7) enabled specific staining of reticular networks in the splenic white pulp and the T cell zone of lymph nodes 23,24 (Figure 1C,D). The ER‐TR7 antibody recognizes collagen type VI 25 and facilitates hence the visualization of the extracellular matrix organization generated by the FRC network. Improved and refined immunohistochemistry protocols and the acquisition of high resolution images by laser scanning confocal microscopy and transmission electron microscopy revealed that the reticular fiber network, that is generated and ensheathed by FRCs, serves as a conduit for soluble factors and antigens 26‐28 .…”
Section: The Fibroblastic Reticular Cell Network—a Brief Historymentioning
confidence: 99%
“…For example, the antibody Erasmus University Rotterdam-thymic reticulum antibody 7 (ER-TR7) enabled specific staining of reticular networks in the splenic white pulp and the T cell zone of lymph nodes 23,24 (Figure 1C,D). The ER-TR7 antibody recognizes collagen type VI 25 and facilitates hence the visualization of the extracellular matrix organization generated by the FRC network.…”
Section: The Fib Rob L a S Ti C Re Ti Cul Ar Cell Ne T Work-a B Rief ...mentioning
confidence: 99%